Drivers of public sector innovation in Poland - Mackiewicz, Marta (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The implementation of innovations in the public sector allows to satisfy public needs and meet socio-economic objectives. Their aim is also to provide services and public goods of higher quality and in an efficient manner, which results in an improved user access to information, faster delivery of services for business and citizens and competitive performance of companies. The purpose of the research paper is to identify the key determinants of innovation in the public sector. The paper presents the analysis of the most important instruments contributing to the development of innovation in the public sector and the mechanisms of improving the quality of management. Among the external drivers of innovation in the public sector much attention has been paid to the European cohesion policy, and the requirements related to the adoption of specific standards. The research methods include literature analysis, logic models illustrating the causal links and individual interviews with the representatives of the central administration.